Art and time: the carving of the main Chapel of the Church of Nossa Senhora Mãe de Deus, in Recife: (Palíndromo, 2023)
The main chapel of the Church of Nossa Senhora Madre de Deus, located in the city of Recife, was decorated with gilded and polychrome carving that illustrates the sacred art of the eighteenth century in the context of Portuguese America. However, the complete absence of records that indicate the course that marked the making of the art for the temple, the officials involved in these tasks and the dates of execution of the works is noteworthy. In the interest of investigating the ornamental constitution of the chancel and discussing its plastic and aesthetic conformation, this work aimed to analyze the decoration of the main chapel of Madre de Deus. Specifically, it sought to systematize the fundamental stages that marked the modification of its ambience, to broaden the understanding of its history, and to attenuate fractions of the innumerable omissions involving the narrative of religious art in Recife. Based on documentary and historical analyses, and theoretical reference that brings together authors such.
Keywords: Church of Nossa Senhora Madre de Deus; restoration; ornamentation